Early-forming Massive Stars Suppress Star Formation and Hierarchical Cluster Assembly - Sean C. Lewis; Stephen L. W. McMillan; Mordecai-Mark Mac Low; Claude Cournoyer-Cloutier; Brooke Polak; Martijn J. C. Wilhelm; Aaron Tran; Alison Sills; Simon Portegies Zwart; Ralf S. Klessen; Joshua E. Wall (The Astrophysical Journal, 2023)
Feedback from massive stars plays an important role in the formation of star clusters. Whether a very massive star is born early or late in the cluster formation timeline has profound implications for the star cluster formation and assembly processes. We carry out a controlled experiment to characterize the effects of early-forming massive stars on star cluster formation. We use the star formation software suite Torch , combining self-gravitating magnetohydrodynamics, ray-tracing radiative transfer, N -body dynamics, and stellar feedback, to model four initially identical 10 ^4 M _⊙ giant molecular clouds with a Gaussian density profile peaking at 521.5 cm ^−3 . Using the Torch software suite through the AMUSE framework, we modify three of the models, to ensure that the first star that forms is very massive (50, 70, and 100 M _⊙ ). Early-forming massive stars disrupt the natal gas structure, resulting in fast evacuation of the gas from the star-forming region. The star formation rate is suppressed, reducing the total mass of the stars formed. Our fiducial control model, without an early massive star, has a larger star formation rate and total efficiency by up to a factor of 3, and a higher average star formation efficiency per freefall time by up to a factor of 7. Early-forming massive stars promote the buildup of spatially separate and gravitationally unbound subclusters, while the control model forms a single massive cluster.